Latihan Senam Kaki Pada Penderita Diabetes Mellitus Dalam Upaya Pencegahan Komplikasi Diabetes Pada Kaki - Aprilia, Desna; Ramadhani, Puput; Nadia, Anggi; Asri, Wienda Sekar; Saputri, Dwie; Handayani, Tita Septi; Rohani, Tuti; Azissah, Danur (LPPM Universitas Dehasen Bengkulu, 2025)
Background: Diabetes Mellitus (DM) is a metabolic disorder that is genetically and clinically heterogeneous with manifestations in the form of loss of carbohydrate tolerance. Physical exercise is one of the four main pillars of DM management. Physical exercise can reduce blood glucose levels because physical exercise will increase glucose use by active muscles. One of the recommended physical exercises is diabetes foot exercises. There are several goals of diabetes foot exercises, namely, improving blood circulation, strengthening small muscles, preventing foot deformities, increasing the strength of the calf and thigh muscles, overcoming limitations in joint movement.Objective: To describe the application of diabetic foot exercises to clients with diabetes mellitus/high risk.Method: The design of this case study is to use a research design using video and newspaper media on foot exercises. Results: The results of the case study show that after doing foot exercises the respondents were able to apply diabetes foot exercises independently. Conclusion: The results of the case study show that clients before being given foot exercises did not know about how to do foot exercises for DM/high risk clients. After being given diabetes foot exercises the client was able to apply the exercises foot.